A brief history of the artist from God to Picasso - Barolsky, Paul (The Pennsylvania State University Press, 2010)
Explores art history and imaginative literature to show how fiction and history inform each other. Traces the modern idea of the artist to the epic tradition from Homer and Ovid to Dante, leading to Michelangelo. Examines how Vasari shaped Balzac's idea of the artist, and Balzac influenced Picasso's --Provided by publisher